2007
DOI: 10.1007/s11104-007-9331-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metal soil pollution and acid rain on growth and water use efficiency of a young model forest ecosystem

Abstract: In a 4-year lysimeter experiment, we investigated the effects of topsoil heavy metal pollution (3,000 mg kg −1 Zn, 640 mg kg −1 Cu, 90 mg kg −1 Pb and 10 mg kg −1 Cd) and (synthetic) acid rain (pH 3.5) on tree growth and water use efficiency of young forest ecosystems consisting of Norway spruce (Picea abies), willow (Salix viminalis), poplar (Populus tremula) and birch (Betula pendula) trees and a variety of understorey plants. The treatments were applied in a Latin square factorial design (contaminated vs un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 40 publications
(36 reference statements)
2
20
0
Order By: Relevance
“…Also, Tognetti et al (2004), Renninger et al (2013), and Salehi et al (2014) found that the studied heavy metals had no toxic effect on photosynthesis in the studied poplar clones. In reality, it can be stated that various physiological responses of poplars exposed to heavy metals can be due to genotype, different growth substrates, plant physiological conditions, type of heavy metal and time periods of exposure to heavy metals (Menon et al 2007;Borghi et al 2008). Kieffer et al (2009) demonstrated that a short-term Cd treatment (14 days) had a strong negative effect on the photosynthetic process, but for a long-term Cd treatment (up to 56 days), this effect was lower.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Tognetti et al (2004), Renninger et al (2013), and Salehi et al (2014) found that the studied heavy metals had no toxic effect on photosynthesis in the studied poplar clones. In reality, it can be stated that various physiological responses of poplars exposed to heavy metals can be due to genotype, different growth substrates, plant physiological conditions, type of heavy metal and time periods of exposure to heavy metals (Menon et al 2007;Borghi et al 2008). Kieffer et al (2009) demonstrated that a short-term Cd treatment (14 days) had a strong negative effect on the photosynthetic process, but for a long-term Cd treatment (up to 56 days), this effect was lower.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy metals mentioned above have negative effects on forest ecosystems, leading to different types of plant damage, like leaf discoloration, increasing tree mortality or significant decreases in tree growth and biodiversity (Menon et al 2007, Fiala et al 2008. Additionally, mercury (Hg) which is also an important trace element emitted to the atmosphere, can influence not only the environment but also human health (Pacyna & Pacyna 2002).…”
Section: Heavy Metalsmentioning
confidence: 99%
“…The pH constitutes the key factor which determines heavy metal availability and toxicity to plants in this particular environment. Any increase in soil acidity may result in heavy metal leaching from soil (Menon et al 2007). Moreover, the trees' reactions to high concentrations of heavy metals can leave them vulnerable to more and more damage caused by different species of fungi and insects (Rademacher 2001).…”
Section: Heavy Metalsmentioning
confidence: 99%
“…The species of Populus used in this experiment, P. tremula is known for its adaptability to a wide range of climate and soil conditions, is highly drought tolerant and may be the world's most widely distributed tree species (Worrell 1995). The B tolerance and accumulation potential of P. tremula has not been evaluated, however P. tremula is tolerant of elevated soil loadings of other trace elements such as Zn and Cd (Dos Santos Utmazian et al 2007;Menon et al 2007a). …”
Section: Phytomanagement Of Boronmentioning
confidence: 99%